Case Report: Evidence of Migratory Silicone Particles Arising From Cohesive Silicone Breast Implants - Mustafá, Jessica C. R.; Fleury, Eduardo de Faria Castro; Dijkman, Henry B. P. M. (Frontiers in Global Women's Health, 2022)
Background Silicone implants have been used since the 1960s for aesthetic purposes and breast reconstructions. During this period, many women have reported up to 40 similar symptoms, including fatigue, the emergence of autoimmune diseases, Raynaud Phenomenon, arthritis, arthralgias, and hair loss, among others. However, most of the time, these symptoms are neglected by doctors across different specialties and are most often considered a psychosomatic disease. Since 2017, many women suffering from the same complaints have formed social media groups to report their histories and subsequently describe the disease as Breast Implant Illness (BII). The phenomenon of gel bleed and silicone toxicity is known and accepted in literature, but silicone migration into the extracapsular space is still poorly demonstrated, due to the difficulty of monitoring its particles and access to patient data. Methods This work demonstrated the presence of silicone through pathological examination in post-explant breast capsules and in the synovial tissue of the right wrist, detected with special Modified Oil Red O (MORO) staining in a patient with a history of BII. The pathological results were compared to the breast MRI imaging files. Results The MRI images show the permeability change of the implant shell diagnosed as a water-droplet signal. It was also possible to diagnose the gel bleeding as the silicone-induced granuloma of breast implant capsule (SIGBIC) in both implants. Silicone gel bleed and migration of silicone were detected with MORO staining in and outside the capsule and in the synovial tissue of the right wrist. Conclusion In this case study, we showed that silicone migration is possible via cohesive silicone gel breast implant leakage. The accumulation of silicone in the synovial tissue of the right wrist suggests local silicone toxicity and defects.